First identification of canine adenovirus 1 in mink and bioinformatics analysis of its 100 K protein - Hou, Jinyu; Xu, Jinfeng; Wang, Ben; Zhang, Hongling; Yin, Baishuang; Li, Goujiang; Lei, Fashou; Cai, Xiaoming; Zhu, Yanzhu; Wang, Longtao (Frontiers in Microbiology, 2023)
Animal trade favors the spreading of emerging canine adenovirus 1 (CAdV-1) in the mink.Because the 100K protein is not exposed to the viral surface at any stage, it can be used to differentiate the vaccine and wild virus infection. However, no related research has been conducted. This study aimed to find evidence of CAdV-1 in the mink and predicted the character of the 100K protein in the current circulating CAdV-1 strain of mink. In this experiment, the identification of CAdV-1, the phylogenetic tree, homology, and bioinformatics analysis of 100K were conducted. The results showed that the CAdV-1 was identified in the mink and its Fiber was located in a separate branch. It was closely related to strains isolated from Norwegian Arctic foxes and Red foxes. 100K was located in a separate branch, which had the closest genetic relationship with skunks, porcupines, raccoons, and hedgehogs, and had a far genetic relationship with the strains in dogs. 100K protein is instability and hydrophobic protein. It had evidence of selective pressure and recombination, 1 glycosylation site, 48 phosphorylation sites, 60 dominant B cell epitopes, and 9 peptides of MHC-I and MHC-II. Its subcellular localization was mainly on the endoplasmic reticulum and mitochondria. The binding sites of 100K protein were DBP protein and 33K protein. The stains in the mink were different from fox. The exploration of its genomic characteristics will provide us with a deeper understanding of the prevention of canine adenovirus.